Effects of Psidium guajava Linn. leaf extract in Japanese subjects with knee pain: a randomized, double-blind, placebo-controlled, parallel pilot study - Kakuo, Shingo; Fushimi, Takashi; Kawasaki, Keiko; Nakamura, Junji; Ota, Noriyasu (Aging clinical and experimental research, 2018)
The extract of Psidium guajava Linn. (guava) leaf was recently revealed to suppress the advance of osteoarthritis (OA) in rat anterior cruciate ligament-transection models. To investigate the efficacy of guava leaf extract in improving knee pain, which is a common symptom of OA, we conducted a double-blind parallel pilot clinical study in Japanese subjects with knee pain. The subjects, who had no medical history of knee treatment, were randomly assigned to two groups with similar total Japanese Knee Osteoarthritis Measure (JKOM) scores. During the 12-week intake period, the subjects in each group ingested 1 g of guava leaf extract (the guava group) or placebo (the placebo group) daily. At week 12, pain and stiffness in knees (one subcategory of JKOM score) in the guava group was significantly lower than that in the placebo group. Using the visual analogue scale (VAS) for knee pain, a significant association between treatment effect and test period was shown, and the guava group had a lower VAS score at week 12 than the placebo group. In conclusion, continuous intake of guava leaf extract might relieve knee pain, suggesting a potential preventive effect against OA symptoms.